2012
DOI: 10.1590/s0034-71672012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Eventos adversos em Unidade de Terapia Intensiva Neonatal

Abstract: ReSUmOEstudo observacional, prospectivo, para determinar a incidência de eventos adversos (EAs) em Unidade de Terapia Intensiva Neonatal (UTIN). Utilizou-se um "instrumento" específico, adaptado do modelo americano utilizado pela Rede Vermont-Oxford. Dos 218 recém-nascidos, 183 (84%) apresentaram EAs, correspondendo a 2,6 EA/paciente. Distúrbios da termorregulação (29%), distúrbios da glicemia (17,1%) e Infecção Relacionada à Assistência à Saúde (IRAS) de origem hospitalar (13,5%) foram os mais frequentes. Alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 24 publications
1
26
1
23
Order By: Relevance
“…O mesmo estudo revelou que 76% dos casos de eventos adversos resultaram em de danos temporários e/ou prolongamento do tempo de internação hospitalar. A referida pesquisa apontou que 87% dos eventos adversos estudados eram preveníveis (17) , considerando-se o que é preconizado pela literatura vigente sobre a identificação do paciente para uma assistência segura.…”
Section: Discussionunclassified
“…O mesmo estudo revelou que 76% dos casos de eventos adversos resultaram em de danos temporários e/ou prolongamento do tempo de internação hospitalar. A referida pesquisa apontou que 87% dos eventos adversos estudados eram preveníveis (17) , considerando-se o que é preconizado pela literatura vigente sobre a identificação do paciente para uma assistência segura.…”
Section: Discussionunclassified
“…A study carried out in a Brazilian NICU identified adverse events in 84% of the newborns hospitalized. Body temperature regulation and blood glucose disorders, and healthcare-associated infections were the most frequent adverse events (7) . Another study with a systematic review on adverse events in NICUs showed a higher occurrence of adverse events associated with incorrect dosage of medication (38%), accidental loss of intravascular catheters (25%), skin injuries (21%), and healthcare-associated infections (20%) (6) .…”
Section: Introductionmentioning
confidence: 99%
“…This study emphasized the importance of improving practices to reduce such incidents. (15) In the present study, the low frequency of reported errors must be considered with caution, as it may have been underestimated. Nursing professionals may have been afraid to admit having caused harm to patients or be unaware that an error had occurred, as the use of technological equipment during work routines is subject to operating anomalies.…”
Section: Discussionmentioning
confidence: 67%